2017
DOI: 10.1371/journal.pone.0169470
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year, In Situ Growth Study on Shallow-Water Populations of the Gorgonian Octocoral Calcigorgia spiculifera in the Gulf of Alaska

Abstract: Gorgonian octocorals are the most abundant corals in Alaska where they provide important structural habitat for managed species of demersal fish and invertebrates. Fifty-nine gorgonian species have been reported from Alaska waters but little is known about their life history characteristics to help us gauge their ability to recover from seafloor disturbance. Colonies of the holaxonian Calcigorgia spiculifera were tagged beginning in 1999 at three sites in Chatham Strait, Southeast Alaska, using scuba and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In this species of gorgonian coral, the growth rates declined logarithmically with age such that younger corals grew faster than older corals. This is consistent with other species of gorgonians [ 32 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this species of gorgonian coral, the growth rates declined logarithmically with age such that younger corals grew faster than older corals. This is consistent with other species of gorgonians [ 32 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…This information could be used by coastal managers to identify which aggregations are most vulnerable to disturbance from human activities, and which should be highlighted for protection. If age and growth characteristics are phylogenetically constrained, as has been suggested for some taxa [ 40 ], then the techniques developed and insights gained in this study could have broader application in the North Atlantic Ocean where another Primnoa species (e. g. P . resedaeformis ; [ 13 , 45 ]) also forms ecologically important habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Growth rates were low compared to other studies, ranging from an average total linear growth (of all branches) of 0.14 (±0.24 SD) cm/year per colony for Paramuricea biscaya colonies at MC344 to 2.5 (±3.2 SD) cm/year for Paramuricea sp B3 at AT357. Image-based studies of shallow-water octocorals have found substantially higher growth rates, up to an average of 2 cm/year per individual branch (Brazeau and Lasker, 1992;Coma et al, 1998;Lasker et al, 2003;Matsumoto, 2004;Stone et al, 2017). Coma et al, (1998) reported that the average growth rate of Paramuricea clavata in the Mediterranean varied between 0.5 and 0.8 cm/year per branch depending on their size, which translated to an average increase of 1.8 cm in colony height every year.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of new branches (growth proportion), the amount of linear growth (growth proportion*total coral size), and both the number of branches that increased in length and the number of newly-formed branches between every consecutive year or between 2012 and 2017 were then estimated for each coral. As very few branches grew on each coral colony, all growth rates indicated in this study represent the total amount of growth detected on each colony, and not the average growth per branch as in several other studies (Brazeau and Lasker, 1992;Coma et al, 1998;Lasker et al, 2003;Matsumoto, 2004;Stone et al, 2017).…”
Section: Growth Measurementsmentioning
confidence: 92%
See 1 more Smart Citation